Looking for structure: Is the two-word stage of language development in apes and human children the same or different? - Patkowski, Mark (Studies in Second Language Learning and Teaching, 2014)
Previously published corpora of two-word utterances by three chimpanzees and three human children were compared to determine whether, as has been claimed, apes possess the same basic syntactic and semantic capacities as 2-year old children. Some similarities were observed in the type of semantic relations expressed by the two groups; however, marked contrasts were also uncovered. With respect to the major syntactic mechanism displayed in two-word child language, namely word order, statistically significant differences were found in all three comparisons that were tested. These results indicate that chimpanzees do not exhibit the linguistic capacities of 2-year old children.